Educational Challenges in Shaping the Entrepreneurship of IT Students - Lupa-Wójcik, Iwona (Przedsiębiorczość - Edukacja, 2020)
One of the key success factors in the IT industry is innovation. It is an integral part of this industry and determines its development and, in addition, there are clear links between innovation and entrepreneurship. Entrepreneurship in the IT industry is of significant economic and social importance as it currently affects virtually every sphere of our lives. This means huge challenges for the education system in the field of entrepreneurship education among future IT specialists. The aim of the article is to analyze entrepreneurial attitudes among IT students, as well as to identify opportunities and barriers to entrepreneurship development in the IT industry in the context of educational challenges. The author formulated the following main research issue: What are the educational challenges in the field of entrepreneurship of IT students? In the research, a survey questionnaire was used for IT students at the Pedagogical University of Krakow. Research has shown that in IT studies, the importance of shaping soft competences, which are necessary for running a business, are largely omitted. They should build confidence, which is very important for people who would like to start their business however are afraid of failure, and it is the main barrier to entrepreneurship development in the IT industry. Creative activities that stimulate business ideas also play an important role in educating entrepreneurship in IT students.